The Influence of Group Guidance Services Based on Problem Based Learning Approach on Improving Students' Critical Thinking Skills - Ghina Rachmawati; Ardimen; Masril; Rahmad Hidayat (Edu Consilium : Jurnal Bimbingan dan Konseling Pendidikan Islam, 2025)
A person's success is not only determined by their intellectual intelligence, but is also determined by their ability to think critically. Meanwhile, conditions in the field found that students had low critical thinking skills. For this reason, students' critical thinking skills need to be improved. One effort to improve critical thinking skills is through group guidance with a problem based learning approach. This type of research uses a quantitative experimental method with a one group pre-test-post-test design. The sample was determined using simple random sampling with a sample size of 10 students. The data collection technique used is a non-test technique using a Likert scale, namely a critical thinking ability scale. The research results show that group guidance with a problem based learning approach has an has a significant effect on increasing students' critical thinking skills as seen from being able to clarify, being able to make assessments, being able to make conclusions, being able to choose strategies.